Ionization States, Cellular Toxicity and Molecular Modeling Studies of Midazolam Complexed with Trimethyl-β-Cyclodextrin - Shityakov, Sergey (Molecules, 2014)
We investigated the ionization profiles for open-ring (OR) and closed-ring (CR) forms of midazolam and drug-binding modes with heptakis-(2,3,6-tri-O-methyl)-β-cyclodextrin (trimethyl-β-cyclodextrin; TRIMEB) using molecular modeling techniques and quantum mechanics methods. The results indicated that the total net charges for different molecular forms of midazolam tend to be cationic for OR and neutral for CR at physiological pH levels. The thermodynamic calculations demonstrated that CR is less water-soluble than OR, mainly due to the maximal solvation energy ([Image: see text] = −9.98 kcal·mol(−1)), which has a minimal [Image: see text] of −67.01 kcal·mol(−1). A cell viability assay did not detect any signs of TRIMEB and OR/CR-TRIMEB complex toxicity on the cEND cells after 24 h of incubation in either Dulbecco’s Modified Eagles Medium or in heat-inactivated human serum. The molecular docking studies identified the more flexible OR form of midazolam as being a better binder to TRIMEB with the fluorophenyl ring introduced inside the amphiphilic cavity of the host molecule. The OR binding affinity was confirmed by a minimal Gibbs free energy of binding (ΔG(bind)) value of −5.57 ± 0.02 kcal·mol(−1), an equilibrium binding constant (K(b)) of 79.89 ± 2.706 μM, and a ligand efficiency index (LE(lig)) of −0.21 ± 0.001. Our current data suggest that in order to improve the clinical applications of midazolam via its complexation with trimethyl-β-cyclodextrin to increase drug’s overall aqueous solubility, it is important to concern the different forms and ionization states of this anesthetic. All mean values are indicated with their standard deviations.